COVID-19: monitoring of respiratory syndromes and home deaths in the Mobile Emergency Care Service (Research, Society and Development, 2020)
This is a cross-sectional study that aimed to analyze the characteristics of respiratory syndromes and home clinical deaths in the Mobile Emergency Care Service of Baixada Fluminense, Rio de Janeiro (2017-2020). Calculating the prevalence and 95% confidence intervals per year of occurrence, univariate and bivariate analyzes were performed. The occurrence rates per million inhabitants were also calculated according to the epidemiological week, discriminating the expected and observed cases for the year 2020. There was an increase of 31.93% in calls for respiratory syndromes with progression of the curve between weeks 11 and 18. The increase in the number of home deaths in the region was 94.5% up to the 27th week, when compared to the same period last year. The progression situation of the death curve was identified between weeks 16 and 19. Considering the characteristics of the calls and the behavior of the epidemiological curve, there is an important progression in cases of respiratory syndromes and home deaths. As it is compatible with the regional epidemiological scenario, it is believed that these indicators allow a quick and simple monitoring of the local behavior of the epidemic, being another instrumental set for the programming of public policies.